(untitled) (Swiss Medical Weekly, 2022)
BACKGROUND: In opioid agonist therapy (OAT) programmes, chronic hepatitis C is highly prevalent and directly observed therapy guarantees optimal adherence. Since 2017, all patients with chronic hepatitis C in Switzerland can be treated with pangenotypic direct-acting antivirals irrespective of liver fibrosis stage. Until the end of 2021, however, prescription was restricted to infectious disease specialists, gastroenterologists and certain addiction specialists. Difficult venous access after long-term intravenous drug use and, in the case of referral to a specialist, difficulties keeping appointments are barriers to HCV diagnosis and treatment. AIMS: To assess whether minimally invasive point-of-care tests and a “test-and-treat / vaccinate on-site” approach can improve human immunodeficiency virus (HIV) / hepatitis C virus (HCV) screening, HCV treatment uptake and immunity against hepatitis A/B. METHODS: Since September 2018, an infectious disease specialist and a study nurse performed 4-weekly visits in the OAT programme “HAG” (heroin dispensation of the canton Aargau), offering HIV/HCV antibody rapid testing (20 min) and HCV RNA quantification (GeneXpert®, 60 min) from capillary blood, noninvasive liver fibrosis assessment (Fibroscan®, 5–10 min) and HCV treatment prescription on-site. Recommended venous blood draws for HAV/HBV serology and HAV/HBV vaccinations were performed by the staff of the “HAG”. Project performance was assessed by annual cross-sectional chart review. RESULTS: Of the 128 patients registered in April 2018, 79 (62%) were still present in May 2021. With 72 newly registered, a total of 200 patients could be assessed, of whom 129 (65%) were still present in May 2021. Between April 2018 and May 2021, the proportion ever tested for HIV antibodies increased from 79% (101/128) to 91% (117/129), the proportion ever tested for HCV antibodies from 83% (106/128) to 93% (120/129) and the proportion of those HCV antibody positive ever tested for HCV RNA tested from 89% (47/53) to 98% (56/57). The proportion with adequate HCV management (last HCV antibody test ≤1 year ago, if HCV antibody negative or last HCV RNA test ≤1 year ago, if HCV antibody-positive and RNA-negative) improved from 23% ([15 + 15]/128) to 80% ([55 + 48]/129). Overall, HCV treatment uptake increased from 60% (21/35) to 92% (55/60) and HCV RNA prevalence among the HCV antibody positives decreased from 38% (18/47) to 7% (6/84). Between 2018 and 2021, 19 non-cirrhotic chronic hepatitis C patients were successfully treated on-site (18 sustained virological responses [SVR] 12, 1 SVR4), with excellent adherence (≥93%) and, so far, no reinfection. The proportion with known HAV/HBV serostatus increased from 38%/51% to 64%/76%. Immunity against HAV/HBV improved from 19%/23% to 50%/57%. CONCLUSION: Capillary blood point-of-care tests and a “test-and-treat / vaccinate on-site” approach remove crucial barriers to diagnosis and treatment, making hepatitis elimination in OAT programmes achievable. A high fluctuation rate requires HIV/HCV/HAV/HBV testing at admission, but also allows more patients to be screened.